Stress distribution in occlusal veneers with different finish lines when applying vertical and tangential forces = Distribución de estrés en carillas con diferentes líneas de terminación aplicando fuerzas verticales y tangenciales - Aliaga, Jimmy
To evaluate stress distribution when applying vertical and tangential forces to 1mm thick occlusal veneers with different finish lines preparations, using the finite element method. One extracted third molar was prepared for occlusal veneers, firstly without any bevel. It was scanned in order to design two groups of lithium disilicate (G1A, G2A) and composite resin (G1B, G2B) occlusal veneers. Then, the third molar preparation was modified, beveling the finish line and it was subsequently scanned again to design the occlusal veneer groups with bevel (LD: G3A, G4A and CR: G3B, G4B). The four groups were subjected to different forces (400 N vertical and 900 N tangential). At 400 N, the non-beveled veneers showed slightly higher Von Mises stress values (G1A: 783 MPa and G1B 736.5 MPa) than the beveled veneers (G3A: 685.7 MPa and G3B: 675.8 MPa). However, when 900 N tangential forces were applied, the beveled occlusal veneers showed higher Von Mises stress values (G4A: 4297 MPa and G4B: 4133 MPa) than the non-beveled occlusal veneers (G2A: 2581.1 MPa and G2B: 3519.1 MPa). Furthermore, it was observed that the tissue under the occlusal veneers with bevel showed higher Von Mises stress values than the models without any bevel. Beveled and non-beveled occlusal veneers of lithium disilicate and composite resin presented similar stress distribution values when vertical forces of 400 N were applied; whereas with tangential forces of 900 N applied near to the finish line, the beveled groups presented notably higher stress values than the non-beveled groups. However, both finish line preparations presented adequate values for possible clinical performance.